IMPLEMENTASI METODE DESIGN THINKING DAN SYSTEM USABILITY SCALE PADA USER EXPERIENCE APLIKASI BELAJAR BAHASA INGGRIS TALKTALES MELALUI CERITA RAKYAT - Muhammad Nabhan Rifa’i; Ramadhan Rakhmat Sani; Suharnawi Suharnawi; Resha Meiranadi Caturkusuma (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
Indonesia faces significant challenges in improving English proficiency among its population. According to the EF Education First English Proficiency Index 2023, Indonesia ranks 79th out of 113 countries. On the other hand, the current generation begins to forget cultural elements such as folklore or myths that have been passed down from the nation's ancestors. This study aims to design an English learning application for children and teenagers using the design thinking method. The stages of design thinking that are used are empathize, define, ideate, prototyping, and testing. In the prototyping stage, low-fidelity and high-fidelity prototypes were created to visualize the application's design and functionality. Testing was conducted by using task scenarios and the System Usability Scale (SUS). The task scenario testing results revealed that the effectiveness and efficiency rate of 85.71%, indicated that most tasks could be completed successfully by users. The SUS testing results showed an average score of 86.5%, indicated that the application has a high level of usability and well-received by users. Thus, the application's interface is considered easy to use and effective in supporting the English learning process for the target users. This research provides a positive contribution to the development of educational applications using a design thinking approach.